Expert review of the multimodal interaction model for Foot Reflexology VRST application - Sulaiman, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Multimodal interactivity has presented numerous advantages to VR which include enhancement of realism, increased efficiency in user task performance and the achievement of an interactivity that is relatively identical to the conventional human to human interactions. Haptic, visual, and aural interactions have been widely utilized and applied in various domains ranging from military and scientific visualization realms into more multidisciplinary areas, like art and culture, education, archeology, and complementary medicine. In Virtual Reality Stress Therapy (VRST) application particularly in the proliferation towards the virtualization and simulation of the Traditional Foot Reflexology (FR) therapy, the multimodal human to human (H-to-H) interactivity involved in foot reflexology was identified and categorized by previous studies from which a design requirement and an interaction model were created. However, model validation using expert reviews is necessary before a final validated interaction model can be obtained. This will translate and lay the foundation for future FR VRST system design. This paper presents an expert review of the multi-modal H-to-H interaction model for FR VRST application using 8 experts from the HCI or related domain. The experts reviewed and gave feedback on the model, their reviews were utilized to reconstruct the multi-modal H-to-H interaction model, consequently yielding a final validated multimodal H-to-H interaction model for FR VRST application. Implications for future research are also discussed. Â© 2016 IEEE.